Antipyretic Efficacy of a Combined Ethanol Extract of Papaya (Carica papaya) and Basil (Ocimum basilicum) Leaves in White Mice (Mus musculus) - Anugrah Umar; Muhummad Rasul Pratama; Nurjaya (Postgraduate, University of Mataram, 2025)
Fever is a condition characterized by an increase in body temperature above 37°C. It typically occurs as a response of the immune system to combat infections caused by bacteria and viruses. Previous studies have shown that papaya leaves (Carica papaya) and basil leaves (Ocimum basilicum) contain flavonoid compounds. Scientifically, the individual extracts of these two plants have demonstrated antipyretic activity. Flavonoids play an important role in inhibiting the cyclooxygenase-2 (COX-2) enzyme in the biosynthesis of prostaglandins (PGE), which act as mediators of fever. This study aimed to evaluate the antipyretic effectiveness of a combination of ethanol extract of papaya and basil leaves in mice induced with 5% peptone. This research employed a true experimental design. A total of 25 male mice were used and divided into five groups: a positive control group (Paracetamol 1.3 mg/20 g body weight), a negative control group (Na-CMC), and three treatment groups receiving combinations of ethanol extract of papaya and basil leaves at doses of 400 mg/kg BW : 200 mg/kg BW (4:2), 600 mg/kg BW : 300 mg/kg BW(6:3), and 800 mg/kg BW : 400 mg/kg BW(8:4), respectively. All treatments were administered orally. Body temperature was measured at 30, 60, and 90 minutes after induction. The results showed no significant difference between the combination treatments and the positive control group, indicating that the combination of ethanol extract of papaya and basil leaves is effective as an antipyretic agent.